Identification Of Accountability With Competence, Community Participation And Information Technology In The Village Of Langkat District - Anggi Pratama; Erlina Erlina; Sirojuzilam Sirojuzilam; Iskandar Muda (UNIVED Press, 2024)
This study aims to examine the effect of village government competence, community participation and utilization of information technology on accountability in villages in the Langkat Regency area. This research design is associative quantitative research. Data collection using a questionnaire with 244 respondents consisting of Planning, Budgeting, Administration, Reporting and Data Compilation in 47 villages in the Langkat Regency area. This research uses the SEM-Partial Least Square (PLS) approach. PLS is a component or variant-based Structural Equation Modeling (SEM) equation model. The results of this study indicate that the competence of village government, community participation and utilization of information technology have a positive effect on the accountability of village financial management. The implications of the results of this study prove that village financial accountability can be identified by factors of village government competence, community participation and the use of information technology that is adopted effectively and on target.